Enhanced antifouling properties of marine antimicrobial peptides by PEGylation - Lou, Tong; Bai, Xiuqin; He, Xiaoyan; Liu, Wencheng; Yang, Zongcheng; Yang, Ying; Yuan, Chengqing (Frontiers in Bioengineering and Biotechnology, 2023)
Covalent immobilisation of antimicrobial peptides (AMPs) on underwater surfaces to combat marine biofouling is of great interest as it is an efficient, broad-spectrum and environmentally friendly strategy. Similar to post-translational modifications of natural proteins, artificial modifications of antimicrobial peptides can introduce important impacts on their properties and functions. The present work revealed the enhanced effect of PEGylation on the antifouling properties of marine antimicrobial peptides (LWFYTMWH) through grafting the modified peptides on aluminium surfaces. PEG was coupled to the peptide by solid-phase peptide synthesis, and the PEGylated peptides were bioconjugated to the aluminium surfaces which was pre-treated by aryldiazonium salts to introduce carboxyl groups. The carboxy group has been activated through the reaction with 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide. The successful modification was confirmed via ATR-FTIR and XPS. Interestingly, the PEGylated peptides modified surfaces showed better antifouling performance against the attachment of Bacillus sp. (Gram-positive) and Escherichia coli (Gram-negative) than those by the original peptides. And, molecular dynamics simulations showed PEGylation could enhance the ability of peptides to destroy membrane. The PEGylated peptides inserted into the membrane and induced the change in local curvature of membrane, leading to the rupture of membrane. The presence of PEG changed the antimicrobial peptides into more flexible conformations and the high hydrophilicity of PEG hindered the settlement of bacteria. These might be the two main working mechanisms for the increased antifouling efficiency of PEGylated peptides modified surface. This study provided a feasible modification strategy of antimicrobial peptides to enhance their antifouling properties.